(untitled) (Journal for Studies in Humanities and Social Sciences, 2017)
This paper presents the results of the study carried out at the University of Namibia on the extent to which high order thinking scaffolding tool can assist students to transfer knowledge. To examine the tool, a quasi-experimental design within the flipped-classroom was used in a mixed method study. Students were divided into two groups, the experimental group and the control group. These two groups were all approached in the similar manner and directed at different times of the day. The only difference was that the experimental group was provided with a scaffolding tool, while the control group had no scaffolding tool. The objective of the study was to evaluate the effectiveness of the Higher Order Thinking as a scaffolding tool that can improve students’ knowledge transfer. When the means were compared, it was found that there is no statistical significant difference between the two means for the Higher Order Thinking Tool group (M= 4.89) and the control group (M= 4.27),